1985
DOI: 10.1007/bf02554834
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prostaglandin E2 in growing rats: Increased metaphyseal hard tissue and cortico-endosteal bone formation

Abstract: To assess the efficacy of PGE2 in inducing in vivo bone formation, graded doses of prostaglandins E2 were administered to 255 g rats. Histomorphometric analyses of selected sequential fluorescent-labeled bones of rats treated with 0, 0.3, 1.0, 3, or 6 mg PGE2/kg/d for 21 days showed that the doses PGE2 depressed longitudinal bone growth, increased growth cartilage thickness slightly, decreased degenerative cartilage cell size and cartilage cell production slightly, and increased proximal tibial metaphyseal har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
98
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(109 citation statements)
references
References 35 publications
10
98
0
1
Order By: Relevance
“…In animal studies it has been suggested that eg prostaglandin E2 (PGE2) and interleukin-1 can induce a dose dependent increase in the subperiostal lamellar bone formation 90 and that subcutaneous injections of PGE2 in growing rats can induce heterotopic bone formation. 91,92 Measurement of 24-h PGE in SCI patients with NHO showed abnormal 24-h PGE2 urinary excretion as long as the bone-scan had not stabilized. 27 However, the mechanism by which prostaglandins may induce ectopic bone formation in SCI patients remains unclear and there are well-known di culties in the interpretation of PGE2 urinary excretion measurements in men presenting with a positive urinary sperm count or in patients with lower urinary tract infections.…”
Section: Local Factorsmentioning
confidence: 99%
“…In animal studies it has been suggested that eg prostaglandin E2 (PGE2) and interleukin-1 can induce a dose dependent increase in the subperiostal lamellar bone formation 90 and that subcutaneous injections of PGE2 in growing rats can induce heterotopic bone formation. 91,92 Measurement of 24-h PGE in SCI patients with NHO showed abnormal 24-h PGE2 urinary excretion as long as the bone-scan had not stabilized. 27 However, the mechanism by which prostaglandins may induce ectopic bone formation in SCI patients remains unclear and there are well-known di culties in the interpretation of PGE2 urinary excretion measurements in men presenting with a positive urinary sperm count or in patients with lower urinary tract infections.…”
Section: Local Factorsmentioning
confidence: 99%
“…An osteocyte-like cell line, MLO-Y4, has been shown to have characteristics of primary osteocytes (27). We and others have shown that MLO-Y4 cells are functionally coupled by gap junction channels and that Cx43 is a major gap junction protein expressed in primary osteocytes and MLO-Y4 cells (8,23,27,36,45,47). Mechanical forces applied to bone cause fluid to flow through the canaliculi surrounding the osteocyte, and that fluid flow shear stress releases prostaglandins and other bone modulators (40) required for bone modeling and remodeling.…”
mentioning
confidence: 97%
“…Prostaglandins are generally thought to be skeletal anabolic agents, because administration of these agents can increase bone mass in various animal species (25)(26)(27), stimulate bone formation in vitro in organ culture (28), and increase nodule formation in rat calvarial osteoblasts (29,30). Prostaglandins also have catabolic effects on bone and have been shown to stimulate osteoclastic bone resorption and osteoclast formation and activation (28,(31)(32)(33)(34).…”
mentioning
confidence: 99%